The Effect of Passion Fruit Concentrate and Ratio of Sugar with Sorbitol on Quality of Red Guava Slice Jam - Christin Uli Munte; Zulkifli Lubis; Lasma Nora Limbong (Jurnal Rekayasa Pangan dan Pertanian, 2014)
This research was aimed to know the effect of passion fruit concentrate and ratio of sugar with sorbitol on the quality of red guava slice jam. This research was conducted using a completely randomized design with two factors, namely the passion fruit concentrate (5%, 10%, 15%, and 20%) and the ratio of sugar with sorbitol (90%:10%, 80%:20%, 70%:30%, and 60%:40%). The parameters analyzed were the level of vitamin C, total acid, total dissolved solids, pH, moisture content, ash content, the strength of the slice jam, hedonic test for color, texture, flavor, aroma, and overall appearance. The results showed that the addition of passion fruit concentrate had highly significant effect on the level of vitamin C, total acid, total dissolved solids, pH, moisture content, the strength of the slice jam, hedonic test for color, texture, flavor, aroma, and overall appearance and a significant effect on ash content. Ratio of sugar and sorbitol gave highly significant effect on level of vitamin C, total acid, total dissolved solids, moisture content, ash content, the strength of the slice jam, hedonic test for taste and overall appearance and gave highly significant effect on the pH, hedonic test for color, texture, flavor, and aroma. Interaction of the two factors gave significant effect on total dissolved solids, hedonic test of the taste and overall appearance. Addition passion fruit concentrate as much as 20% and the ratio of sugar with sorbitol (70%:30%) produced the best quality of red guava slice jam. Keywords: Passion Fruit, Red Guava, Slice Jam, Sorbitol